(untitled) (Journal of the College of Basic Education, 2022)
Social media is one of the most important risks for many families, despite the positive aspects it bears that no one can deny. However, it carries with it many dangers that are difficult to ignore due to its impact on its members. These means have negatively affected family relations and contributed to changing behavior. Her children, and in order to verify the dangers of social media on family relations, the two researchers selected a simple random sample of (80) families of male and female employees in the Bab al-Mu’azzam college complex, of different ages.